Vitamin A status of the minority ethnic group of Karen hill tribe children aged 1-6 years in Northern Thailand - Prasong Tienboon (2018)
Vitamin A deficiency (VAD) is the most common cause of childhood blindness in the developing world. It is estimated that by giving adequate vitamin A, in vitamin A deficient populations, child mortality from measles can be reduced by 50%, and mortality from diarrheal disease by 40%. Overall mortality in children 6-59 months of age can be reduced by 23%. This paper reported results from a study of vitamin A status and malnutrition of the minority ethnic group of Karen hill tribe children aged 1-6 years in the north of Thailand. All children aged 1-6 years (N = 158; 83 boys, 75 girls) from the three Karen villages (Mae Hae Tai, Mae Yot, Mae Raek) of Mae Chaem district in the north of Thailand were studied. The Karen is the largest mountain ethnic minority ("hill tribe") group in Thailand. All children were examined by a qualified medical doctor and were assessed for their vitamin A intakes using 24 hours dietary recall. Thai food composition table from Ministry of Health, Thailand were used as references. The results were compared with the Thai Recommended Dietary Allowances. Children aged 1-3 years and 4-6 years were separately analysed due to the differences in Thai Recommended Dietary Allowances between the two age groups. A whole blood of 300 μL was obtained by "fingerstick" for determination of serum vitamin A. Community or village's vitamin A status was assessed by using Simplified Dietary Assessment (SDA) method and Helen Keller International (HKI) food frequency method. Descriptive statistics were used to analyse the data. All families of the study boys and girls had income lower than the Thailand poverty line (US $ 1,000/year). On average, 63% of children from Mae Hae Tai village, 1.5% of children from Mae Yot village and none of children from Mae Raek village had serum vitamin A <0.7 μmol/L which indicated VAD. All boys and only girls from Mae Raek village consumed vitamin A more than the Thai RDA but girls from Mae Hae Tai village and Mae Yot village consumed vitamin A less than the Thai RDA. Both boys and girls from Mae Raek village and also girls from Mae Yot village consumed vitamin A more than the Thai RDA. Using SDA and HKI methods to assess vitamin A status of the villages to see whether VAD is a village's nutritional problem, it was found that all children from the three villages were at risk of VAD. In order to improve vitamin A status of the Karen children in Mae Chaem district, recommendations were made as follow: (1) increased use of fat and oil, particularly in areas with high risk of VAD; (2) more general work with Karen communities on how children's diets might be improved in a culturally acceptable manner, so as to bring vitamin A consumption closer to recommended allowance level.